ANALISIS LOSSES PIPA LURUS BERDIAMETER 40 cm PADA TEROWONGAN ANGIN LAPAN - Ahmad Jamaludin Fitroh (Jurnal Teknologi Dirgantara, 2011)
One of LAPAN’s programs is design and build the ramjet open tested wind tunnel. The lenght of pipe connecting between wind tunnel and storage tank was designed long enough so it was estimated there is big losses along the pipe. The object of this research is to calculation that losses, specially for the straight part only. The magnitude of the losses was gotten from simulation using software based on CFD theory. This research used two methods, i.e. based on pressure method and based on mass flow rate method. The simulation’s result using based on mass flow rate method gave the higher losses for the straight pipe so that result was chosen as the final result. That result was processed become the losses as a function of mass flow rate. The higher mass flow rate will produce the bigger losses. At mass flow rate of 60 kg/s, the losses is 0.135 %/m and at 100 kg/s the losses is 0.299 %/m. The relation between both parameter is close to linier curve. Key word:Pipe, losses, CFD, wind tunnel